Monte Carlo simulation of the response functions of CdTe detectors to be applied in x-ray spectroscopy. (June 2015) - Tomal, A.; Santos, J.C.; Costa, P.R.; Lopez Gonzales, A.H.; Poletti, M.E.
Abstract: In this work, the energy response functions of a CdTe detector were obtained by Monte Carlo (MC) simulation in the energy range from 5 to 160 keV, using the PENELOPE code. In the response calculations the carrier transport features and the detector resolution were included. The computed energy response function was validated through comparison with experimental results obtained with 241 Am and 152 Eu sources. In order to investigate the influence of the correction by the detector response at diagnostic energy range, x-ray spectra were measured using a CdTe detector (model XR-100T, Amptek), and then corrected by the energy response of the detector using the stripping procedure. Results showed that the CdTe exhibits good energy response at low energies (below 40 keV), showing only small distortions on the measured spectra. For energies below about 80 keV, the contribution of the escape of Cd- and Te-K x-rays produce significant distortions on the measured x-ray spectra. For higher energies, the most important correction is the detector efficiency and the carrier trapping effects. The results showed that, after correction by the energy response, the measured spectra are in good agreement with those provided by a theoretical model of the literature. Finally, our results showed that the detailed knowledge of the response function and a proper correction procedure are fundamental for achieving more accurate spectra from which quality parameters (i.e., half-value layer and homogeneity coefficient) can be determined. Abstract : Highlights: The response function of a CdTe detector was determined by Monte Carlo simulation. The simulation takes into account all interaction process, the carrier transport and the Gaussian resolution. The influence of different effects of spectral distortion was investigated. CdTe detector was applied for x-ray spectroscopy. The proper correction procedure is needed to achieve realistic x-ray spectra.